Optimal bladder diary duration for patients with suprapontine neurogenic lower urinary tract dysfunction - Konstantinidis, Charalampos; Kratiras, Zisis; Samarinas, Michael; Skriapas, Konstantinos (International Brazilian Journal of Urology, 2016)
To identify the minimum bladder diary's length required to furnish reliable documentation of LUTS in a specific cohort of patients suffering from neurogenic urinary dysfunction secondary to suprapontine pathology. From January 2008 to January 2014, patients suffering from suprapontine pathology and LUTS were requested to prospectively complete a bladder diary form for 7 consecutive days. Micturitions per day, excreta per micturition, urgency and incontinence episodes and voided volume per day were evaluated from the completed diaries. We compared the averaged records of consecutive days (2-6 days) to the total 7 days records for each patient's diary, seeking the minimum diary's length that could provide records comparable to the 7 days average, the reference point in terms of reliability. From 285 subjects, 94 male and 69 female patients enrolled in the study. The records of day 1 were significantly different from the average of the 7 days records in every parameter, showing relatively small correlation and providing insuficiente documentation. Correlations gradually increased along the increase in diary's duration. According to our results a 3-day duration bladder diary is efficient and can provide results comparable to a 7 day length for four of our evaluated parameters. Regarding incontinence episodes, 3 days seems inadequate to furnish comparable results, showing a borderline difference. A 3-day diary can be used, as its reliability is efficient regarding number of micturition per day, excreta per micturition, episodes of urgency and voided volume per day.